HUBUNGAN ANTARA KEMAMPUAN BERKOMUNIKASI GURU DAN MINAT BELAJAR SISWA - Sudarto Sudarto; Rosmalah Rosmalah; Muhammad Rizky Muhammad Rizky (JISOS: JURNAL ILMU SOSIAL, 2022)
This study aims to determine the correlation between the teacher communication skills and the learning student interest of the Fouth Grade at SD Negeri 22 Jeppe'e, Tanete Riattang Barat District, Bone Regency. The populations of this study were the entire fourth grade of students at SD Negeri 22 Jeppe'e, Tanete Riattang Barat District, Bone Regency, Academic Year 2021/2022, in totaling 86 people. The data analysis technique was inferential statistical analysis. Based on the results of inferential statistical analysis we foud that tcount (16.7552) > ttable (2.0126) at a significant level of 0,05 which means H0 was rejected and H1 was accepted. The results of the study could be concluded that there was a significant correlation between the teacher communicating ability and the learning student’s interest of the Fourth Grade at SD Negeri 22 Jeppe'e, Tanete Riattang Barat District, Bone Regency.